ANALISIS JALUR TERHADAP FAKOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA - Yuni Nurkuntari; Fatkhurokhman Fauzi; Moh Yamin Darsyah (Universitas Muhammadiyah Semarang, 2017)
Human development index (HDI)is one of the benchmarks of human development in an area, where the area is said to be advanced or not seen from the index of human development. Where in the index of human development itself is influenced or formed in theory published by Badan Pusast Statistik itself is formed by three basic components of life expectancy index where indicator is life expectancy, education index with indicator that is average of school length and school long expectation , and the standard living index is eligible to take customized per capita expenditure indicators. In the regression or correlation method is only limited in knowing whether or not the influence or relationship but themodel obtained in accordance or not no further information. However there is a direct and indirect test of path analysis. So in this research will study about path analysis on Human Development Index (HDI) in West Java Province. Before testing the suitability of models there are assumptions that must be met, among others, normality, autocorrelation, multikolinier, heteroseksdastisitas. Unfulfilled assumptions include heterosexuality and aoutocorrelation. However, the test for suitability of the model tested is very accurate as shown by the Minimum Fit Function value of Chi-Square = 0.00 (P = 1.00000) because the minimum Chi-Square value and P-value value of 1> 0.05 means the model is correct. With a relationship or a large correlation between X_1 with Y, X_3 with Y and X_4 with Y.Relationships are all there are relationships and variables have significant parameters.Key words: HDI, Correlation, Path Diagram, Path Analysis